PENGARUH KAPABILITAS TEKNOLOGI INFORMASI TERHADAP KUALITAS INFORMASI AKUNTANSI MANAJEMEN DENGAN KETIDAKPASTIAN TEKNOLOGI SEBAGAI VARIABEL MODERASI - Eliada Herwiyanti (Dinamika Akuntansi Keuangan dan Perbankan, 2014)
This study aims to determine the effect information technology capability and quality of management accounting informationwith technological uncertainty as moderating variable. The highest business competition requires companies to be able tooptimize their resources. Company with information technology capability will able to produce good quality of information.The existence of changes in the external environment related to the rapid development of technology and uncertain technologyrequire companies to be able to respond precisely. Thus, the existence of technological uncertainty will stronger therelationship between information technology capability and quality of management accounting information. Data werecollected from companies that listed in Indonesia Stock Exchange. Respondent represented by accounting manager as of 95people were participated in filling out the questionnaire. Then, the data processed using SEM analysis technique. Thescreening stage of the data generated 94 responses that were used for decision making of the results study. Data processing hasbeen done using the software SPSS 16.0 and WarpPLS 4.0. The result of this study supports the hypothesis that states there arepositive effect of information technology capability toward quality of management accounting information. Whereas, thehypothesis that states technological uncertainty moderates the relationship between information technology capability andquality of management accounting information is not supported. This study is limited to the lack of connection between thevariables in the study due to the lack of the data and heterogeneous of the sample type selection.Keywords: information technology capability, technological uncertainty, quality of management accounting information